THE INFLUENCE OF LEARNING MODEL USAGE OF TWO-STAY TWO-STRAY TO STUDENT’S LEARNING OUTCOME ON ENGINE AND COMPONENT SUBJECT IN CLASS X TKR SMK NEGERI 1 PALANGKA RAYA AT ACADEMIC YEAR 2015/2016 - Sugianto; Sri Murwantini (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
The learning tought by teacher greatly determines the successful learning however many educationalists are still holding the learning process and activity as the ordinary knowledge transfered by teacher to students. It is frequent in which the learning strategy is only giving the information without involving students actively in learning culture. Consequently, many students are inactive in learning and event doing juvenile delinquency at school thus lacking in understanding to learning subjects such as engine and component subject. Therefore, this research posseses a purpose to discover the influence of Two-Stay Two-Stray learning model usage to student’s learning outcome for engine and component subject in class X TKR SMK Negeri 1 Palangka Raya at academic year 2015/2016. Based on the result of research is known that there is the enhancement of student’s learning outcome after applying Two-Stay Two-stray learning model usage in which the average score of posttest for experimental group and control class are respectively at 78,4 and 66,13. By prerequisite analysis test on normality test is that posttest score for experimental class and control class was distributing normally and hypothesis test used t-test was obtained the value thitung> ttabel (7,26 > 1,67). On those values, it can be known that Ho was accepted and Ho rejected. All in all, this can be concluded that there are the effect of Two-Stay Two-stray learning model usage to student’s learning outcome for engine and component subject in class X TKR SMK Negeri 1 Palangka Raya.